2012
DOI: 10.1097/mot.0b013e32834ee6e5
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the envelope

Abstract: The incentives for living donor transplants are to eliminate long-wait times for a deceased donor organ and to improve outcomes. With both the incentive is high, but either by itself is sufficient. As the number of pancreas transplant candidates increase, so will wait times for a deceased donor organ. For this reason, living donor pancreas/islet transplant volume will likely increase in the years to come.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Typically both organs come from the same donor, although rarely the organs come from separate deceased donors and even less commonly one or both organs come from a living donor. [25][26][27] Pancreas after kidney transplant (PAK) The second type of pancreas transplant is a PAK. The relative advantage of this approach for patients with diabetes and renal failure is to avoid or minimize the morbidity and mortality associated with dialysis therapy by p roviding a living donor kidney transplant followed by a deceased A brief history of pancreas transplantation Kelly and colleagues performed the first successful pancreas transplant in a human at the University of Minnesota, USA, in 1966.…”
Section: Simultaneous Pancreas-kidney Transplant (Spk)mentioning
confidence: 99%
“…Typically both organs come from the same donor, although rarely the organs come from separate deceased donors and even less commonly one or both organs come from a living donor. [25][26][27] Pancreas after kidney transplant (PAK) The second type of pancreas transplant is a PAK. The relative advantage of this approach for patients with diabetes and renal failure is to avoid or minimize the morbidity and mortality associated with dialysis therapy by p roviding a living donor kidney transplant followed by a deceased A brief history of pancreas transplantation Kelly and colleagues performed the first successful pancreas transplant in a human at the University of Minnesota, USA, in 1966.…”
Section: Simultaneous Pancreas-kidney Transplant (Spk)mentioning
confidence: 99%
“…Perioperative risks have been described, and observed rates of bleeding and the risk of splenectomy range from 5% to 15%. 5,7 However, less is known about the long-term medical outcomes. By linking the national US donor registry with pharmaceutical fill records, we found that 26.7% of living pancreas donors filled diabetes medications or supplies over a mean post-donation follow-up period of 16 years, including use of insulin or an oral agent in 20%.…”
Section: Discussionmentioning
confidence: 99%
“…These observations led to changes in the center’s criteria for acceptance of living pancreas donors in 1997, incorporating abnormal predonation glucose tolerance tests, a history of gestational diabetes mellitus, or elevated body mass index at the time of donation as exclusion criteria. 7 In a more recent study from the same institution after this policy change, Kumar et al reported that 20% (3/15) of living pancreas donors between 1997 and 2003 had developed PDDM after a mean follow-up period of 5 years by evaluation including glucose tolerance testing; however, only 13% were on diabetic medications at the time of follow-up, while 28% (6/21) of the original cohort were lost to follow-up. 10 An additional 46% (6/15) of the followed pancreas donors were found to have impaired fasting glucose and/or impaired glucose tolerance after metabolic assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Scientific Registry of Transplant Recipients (SRTR), the 1-year rate of graft survival is 86% when a pancreas and a kidney are transplanted together (SPK), 82% when pancreas is transplanted after kidney (PAK) and 75% when pancreas is transplanted alone. Most pancreatic grafts are from cadaveric donors, though transplantation of a segment of the pancreas donated by a living donor has also been reported (6). Transplantation, however, requires major surgery and dependence on life-long immunosuppression to prevent graft rejection.…”
Section: Therapeutic Options For Type 1 Diabetesmentioning
confidence: 99%